Brachial-ankle pulse wave velocity predicts liver volume in patients with autosomal dominant polycystic kidney disease - Wasako Tato; Tatsuya Suwabe; Yoshifumi Ubara; Yuki Oba; Hiroki Mizuno; Daisuke Ikuma; Masayuki Yamanouchi; Noriko Inoue; Akinari Sekine; Kiho Tanaka; Eiko Hasegawa; Takehiko Wada; et al. (PLoS ONE, 2025)
Background Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disease and Polycystic liver disease (PLD) is the most common extrarenal manifestation of ADPKD. Various non-inherited factors have been reported to affect total kidney volume (TKV) in ADPKD. However, the non-inherited factors affecting liver volume (LV) in ADPKD are unknown. Methods We aimed to identify the factors affecting LV and TKV in ADPKD; and to analyze the relationship between changes in these parameters and arterial stiffness, assessed using brachial-ankle pulse wave velocity (baPWV). Results We enrolled 165 patients (66 men and 99 women; mean age 47.3 ± 6.9 years). Univariable analysis revealed that sex, mean baPWV, ΔbaPWV, tolvaptan use, hyperlipidemia, hyperuricemia, Hb concentration, eGFR, proteinuria, and height-adjusted TKV (htTKV) were significantly associated with height-adjusted LV (htLV) at baseline. Multivariate analysis showed that sex, BMI, ΔbaPWV, and tolvaptan use were significantly associated with htLV at baseline. The baseline htLV correlated with ΔbaPWV (r = 0.32, p < 0.0001). Univariable linear mixed model analysis revealed that sex, mean baPWV, ΔbaPWV, tolvaptan use, hyperuricemia, Hb concentration, eGFR, and proteinuria significantly affected the change in htLV. Multivariate linear mixed model analysis revealed that sex, BMI, and tolvaptan use significantly affected the change in htLV. The change in the htLV ratio was larger in patients with a higher ΔbaPWV (p < 0.0001). Whereas, ΔbaPWV was not a significant factor for the baseline htTKV and the changes in htTKV in univariable and multivariable analysis. Conclusions We have shown that ΔbaPWV is a predictor of baseline htLV, and the chronological changes in htLV in patients with ADPKD.